The Spanish social tariff and renewable energy cooperatives: situation and perspectives - Jaio Gabiola, Egoitz; Paredes Gázquez, Juan Diego; Sánchez Rodríguez, José Antonio (REVESCO. Revista de Estudios Cooperativos, 2016)
Social tariffs are, along with transfer payments and energy efficiency measures, an instrument to alleviate energy poverty. The name of the Spanish social tariff is “bono social”, and it was established in 2009. To qualify for bono social, the electricity consumer should meet any of the socioeconomic requirements stipulated by law and contract the electricity supply with a “comercializadora de referencia”, companies that are required to offer the bono social by law.Renewable energy cooperatives, a recent phenomenon in Spain, are not comercializadoras de referencia, so they are not obliged to offer the bono social. This does not mean there are no cooperative members at risk of energy poverty or vulnerable consumers.This study has two objectives. The first is to sketch the socioeconomic profile of members of the renewable energy cooperatives. The second is to analyze if these members are entitled to the bono social, or would be to other subsidized prices with different requirements to those of the bono social.For this purpose, we conducted a survey to members of the largest renewable energy cooperative in Spain, Som Energia. The results show that the members of renewable energy cooperatives are exposed to energy poverty risk, although its reach depends on the definition of vulnerable consumer.
Keywords: Cooperative societies; social tariffs; energy poverty; electricity; renewable energies